TRADISI OTONAN BOJOG PURA DALEM AGUNG PADANGTEGAL DI DESA PEKRAMAN PADANGTEGAL KECAMATAN UBUD KABUPATEN GIANYAR : Kajian Bentuk, Fungsi dan Makna (Genta Hredaya: Media Informasi Ilmiah Filsafat Hindu, 2025)
In connection with the traditions found in Bali, as is the case in Pakraman Padangtegal Village, Ubud District, Gianyar Regency has the Otonan Bojog Tradition which is carried out every Tumpek Kandang or Tumpek Uye, which is seen as having a unique and distinctive tradition seen from the upakara and ceremonies carried out from generation to generation as a local religious treasure for the people of Pakraman Village, Padangtegal. However, most of the wider community and the younger generation are less interested in witnessing and following the implementation of the otonan Bojog tradition, most of the young people and the public only know or don't even know at all what the function and meaning of the implementation of the otonan Bojog tradition is. Based on the background above, in this research there are three problems that will be discussed, including: (1) What is the form of the Bojog Otonan Tradition? (2) What is the function of the Bojog Otonan Tradition? (3) What is the meaning of the Bojog Otonan Tradition? This research aims to determine (1) the form of the Bojog Otonan Tradition, (2) the function of implementing the Bojog Otonan Tradition and (3) the meaning of the Bojog Otonan Tradition. The data collection methods used in this research are: observation, interviews, documentation and literature. The collected data was analyzed using a qualitative descriptive analysis method with steps, namely data reduction, data classification and drawing conclusions. The results of the analysis show and conclude that: (1) The series of Bojog Otonan traditions begins with the people of Pakraman Village in Padangtegal going to Pura Dalem Agung Padangtegal to mendak tirtha which was performed by Mangku Dalem. Followed by carrying out a quest at the Monkey Forest T-junction. After the pecaruan is finished, it is continued by distributing chicken eggs, rambutan fruit and papaya leaves to the bojog-bojog while the officials sprinkle tirtha on the bojog. (2) The function of implementing the Bojog Otonan Tradition is as an otonan ceremony for the bojog-bojog located in the Mongkey Forest area of ​​Ubud, If the Otonan Bojog Tradition is not implemented, it is feared that it will have a bad impact on the people of Pakraman Village, Padangtegal, because the people believe that the bojog found in Mongkey Forest is a sacred bojog due. Apart from that, it also has meanings including: 1) The meaning of the Bojog Otonan Tradition Ceremony and Upakara, is to purify the Atman of the bojog-bojog in the Mongkey Forest area and to ask Ida Sang Hyang Widhi Wasa to give a gift to the village wewengkon (region). Pakraman Padangtegal becomes safe, peaceful and harmonious. 2) The meaning of the Bojog Otonan Tradition, is as an application of the Tri Hita Karana concept, and to preserve the Bojog Otonan Tradition so that it does not become extinct. 3) The meaning of Tattwa, is how village customs believe in the existence of a manifestation of God whom they worship as Rare Angon and Deva Rudra to ask for salvation and to neutralize negative traits and make the most of it to create harmony and balance in Parahyangan (human relationship with God), Pawongan (human relations with humans) and Pabelasan (human relations with the environment). 4) The meaning of ethics, in implementing the Bojog Otonan Tradition, it must be based on a feeling of sincerity and sincerity in its implementation, solely a sense of devotion and devotion to Ida Sang Hyang Widhi Wasa so that the aims and objectives of implementing the Bojog Otonan Tradition can be achieved.
Keywords: bojog otonan tradition; form; function; meaning